The economic evaluation of road investment in the Republic of Ireland - Barrett, Sean D. (Statistical and Social Inquiry Society of Ireland, 1976)
This paper addresses the question "How much money should be spent on road improvement over the next twenty years?". It examines the factors that influence the answers to the question as it applies to the national primary route network in the Republic of Ireland.
Read before the Society, 23 October 1975
Keywords: Transport policy; Road investment; Irish infrastructure; 314.15